Novel peptides contribute to the antimicrobial activity of camel milk fermented with Lactobacillus plantarum IS10 - Algboory, Hussein L.; Muhialdin, Belal J. (Elsevier, 2021)
Fermented camel milk is a good source of peptides including novel peptides produced by the starter culture. This study aimed to determine the novel peptides that contribute to the antimicrobial activity of fermented camel milk. Camel milk was pasteurized at 90 ◦C for 30 min and fermented with Lactobacillus plantarum IS10 for 24 h at 42 ◦C. The water-soluble extract was subjected to RP-HPLC fractionation and LC-MS/MS in combination with PEAKS STDIO software to identify the novel peptides via de novo sequencing. The antimicrobial activity was determined using a 96-well microtiter plate assay, showing a significant decline in pH from 6.6 at 0 h to 4.1 at 24 h with an increasing L. plantarum cell count from Log10 5.5 CFU mL− 1 at 0 h to Log10 7.4 CFU mL− 1 at 24 h. Twenty-one fractions were obtained by RP-HPLC, with fraction 14 demonstrating the highest antibacterial activity towards Escherichia coli and Staphylococcus aureus subsp. aureus. Fraction 14 contained 30 novel peptides with a molecular weight ranging from 598 to 2053 Da, with seven peptides showing more than 50% similarity to antimicrobial peptides contained in the database. The seven novel peptides inhibited the growth of E. coli and S. aureus subsp. aureus, contributing to the antimicrobial activity of fermented camel milk.